2011
DOI: 10.1556/amicr.58.2011.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prevalence of Demodex mites in young adults

Abstract: Demodex mites are ectoparasites often found in follicles of facial skin. Their role in human diseases is under investigation, and a growing number of studies indicated that they contribute to chronic inflammatory conditions of the skin, such as rosacea, blepharitis, otitis externa, alopecia and folliculitis. In our study we tested 96 healthy adults for the presence of Demodex mites. Risk factors influencing presence of mites and skin types of the tested individuals were evaluated. We found Demodex folliculorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
1
22
0
3
Order By: Relevance
“…Several recent reports had shown the prevalence of Demodex [19,20], in patients and age groups [21] and in patients with ocular discomfort [12]. In our study, we found that Demodex were more frequent in elderly people (76-105 years) and the frequency was lower in individuals ranging 15-75 years.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Several recent reports had shown the prevalence of Demodex [19,20], in patients and age groups [21] and in patients with ocular discomfort [12]. In our study, we found that Demodex were more frequent in elderly people (76-105 years) and the frequency was lower in individuals ranging 15-75 years.…”
Section: Discussionsupporting
confidence: 64%
“…So variations of the skin could facilitate the establishment of mites in this ocular zone, but also in the skin. Recently, there was found a prevalence of 17% of Demodex in young adults [20] and found that people with Demodex described dry skin, more prone to erythema but less for folliculitis. In our study, there was no difference between individuals with Demodex, since 49% and 51% were symptomatic and asymptomatic, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Raszeja-Kotelba et al [20] and Forton et al [21] have given a higher intensity of infection in women than in men, which was attributed to the use of creams and powders as well as being influenced by sex hormones. However, Horváth et al [22] observed that the infection rate was higher in men than in women. Yamashita et al [23] and Kuźna-Grygiel et al [14] as well as Wesołows-ka et al [16] did not find a relationship between sex and the prevalence of Demodex spp.…”
Section: Epidemiologymentioning
confidence: 97%
“…Corneal manifestations of demodicosis, such as corneal vascularization, infiltration, corneal opacity, and corneal scars, are believed to be secondary to blepharitis. 14,16 Demodex mites may act as a triggering factor in eyelid basal cell carcinoma due to their ability to cause chronic inflammation. Diagnosis of demodicosis involves microscopic detection of mites from skin, hair, or eyelash.…”
Section: Demodiciosismentioning
confidence: 99%